2013
DOI: 10.2355/isijinternational.53.403
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Effect of Hyper-coal on Ferro-coke Strength Index

Abstract: The relationship between the strength and the microstructure of ferro-coke with hyper-coal (HPC) addition is investigated. In particular, we focused on the adhesiveness of coal particles. The strength of ferrocoke was evaluated by a tensile strength test and coke microstructure with increasing the amount of HPC addition was observed. In the observation of the microstructure, absolute maximum length and roundness of pores were measured. The result indicated that the strength of ferro-coke increases with an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
0
20
0
2
Order By: Relevance
“…11) Moreover, Uchida et al indicated that blending HPC into coal particles enhanced adhesiveness of coal particles and strength of coke while strength of coke decreased because adhesiveness of coal particles decreased due to the existence of metallic iron around coal particles in microscopic structure of ferro-coke. 12) These studies evaluated coke samples after carbonization and focused on the relationships between only two components, coal and iron or HPC. To investigate ferro-coke utilized in industrial processes, the evaluation of three components, coal, iron ore, and HPC is required.…”
Section: Effect Of Hpc (Hyper-coal) On Strength Of Ferro-coke During mentioning
confidence: 99%
See 1 more Smart Citation
“…11) Moreover, Uchida et al indicated that blending HPC into coal particles enhanced adhesiveness of coal particles and strength of coke while strength of coke decreased because adhesiveness of coal particles decreased due to the existence of metallic iron around coal particles in microscopic structure of ferro-coke. 12) These studies evaluated coke samples after carbonization and focused on the relationships between only two components, coal and iron or HPC. To investigate ferro-coke utilized in industrial processes, the evaluation of three components, coal, iron ore, and HPC is required.…”
Section: Effect Of Hpc (Hyper-coal) On Strength Of Ferro-coke During mentioning
confidence: 99%
“…This would indicate that thermoplastic components of coal were decomposed due to catalysis of hematite, and the adhesiveness of coal particles decreased. In the previous study, Uchida et al 12) defined pores with roundness of less than 0.05 as non-adhesion pores with iron particles between coal particles in experiments with ferro-coke combined with HPC, and reported that adhesiveness of coal particles can be evaluated by finding the pores with roundness of less than 0.05. In the present study, the existence ratio of pores with roundness of less than 0.05 was used as index of the adhesiveness.…”
Section: Adhesiveness Of Coal Particles In Semi-cokementioning
confidence: 99%
“…HPC begins to soften at low temperature, shows a high fluidity, and demonstrates the possibility of enhancing coke strength by blending with low-rank coals. 10) Uchida et al 11) reported that iron oxide occupies the spaces between coal particles in ferro-coke and inhibits the adhesiveness of coal particles. However, these researchers also showed that blending HPC in ferro-coke enhances the adhesiveness of coal particles as well as coke strength and summarized that the adhesiveness of coal particles is one of the dominant factors in coke strength.…”
Section: Effect Of Iron Ore Reduction On Ferro-coke Strength With Hypmentioning
confidence: 99%
“…The tensile strength of the samples carbonized at 1 000°C is measured using the same diametral compression test used previously, 11) and the scale parameters are evaluated by Weibull plots. A total of 14 or 15 tests are conducted for each condition.…”
Section: Evaluation Of Coke Strength After Carbonizationmentioning
confidence: 99%
“…Uchida et al 12) reported that although the strength of ferro-coke decreased because the iron particles inhibited coal particles adhesion, the strength of ferro-coke with added HPC increased because the coal particle adhesion was improved. Kannari et al 13) reported that the fluidity of coking coal with added Fe2O3 decreased, because the tolueneinsoluble and pyridine-soluble fractions of the coking coal were decomposed by the Fe2O3.…”
Section: Introductionmentioning
confidence: 99%